P 135 - The effect of low back pain on lower extremity alignment during squat - YILDIZ ÖZER, AYSEL; TİMURTAŞ, EREN; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (Elsevier B.V., 2018)
[No abstract available]